(untitled) (Journal of Hama University, 2022)
This study was carried to investigate the effect of adding of thymus and rosemary powder to broiler standard diet, on some productive performance. One hundred and four one-day old Ross strain unsexed chicks were randomly distributed into four groups (26 chicks for each) and each group were divided into two replicates (13 chicks for each), as flowing: First group is control without any addition, second and third groups included the addition of 1 g thymus powder/kg diet and 1 g rosemary powder/kg diet respectively, and the fourth group included the addition of mixture of one-gram thymus and one-gram rosemary powder/kg diet. The results showed significantly (P<0.05) positive effect on the body weight gain, amount of feed consumption and feed conversion rate compared with control group at end of experiment (36 days). The data is showed also improvements of carcass quality with significantly difference between second and third treatment groups compared with the control group. However, the beast improving in productive performance was obtained in chicks fed 1 g thymus powder/kg diet.